The Role of the Illustrator in the Age of AI: The Importance of Visual, Local, Cultural, and Historical Repertoire in the Creative Process of Children’s Book Illustrations - Rampinelli, Maria Clara Marins; Torres, David Ruiz (Farol, 2026)
Regarding the illustrations found in contemporary children’s literature—a landscape shaped by generative artificial intelligence (GenAI) tools—a cautious examination of the creative possibilities inherent in their visual conception is warranted. The readership relies on these illustrations to interpret the written narrative, which achieves full meaning through the dialogue mediated by the image. In this context, the figure of the illustrator and their distinctly human presence come to the fore; this text highlights the value of a subjective repertoire as an essential component of creating illustrations for children’s literature, analyzing two books—one produced with GenAI and one without.